Cuban scientific production on diabetes, 2000–2017: Peer-reviewed Publications, Collaboration and Impact - Corrales Reyes, Ibraín Enrique (2019)
INTRODUCTION The steadily increasing prevalence of diabetes globally has captured researchers’ attention. Cuban production of scientific articles on diabetes has not been studied from a bibliometric perspective. OBJECTIVE Characterize the production and impact of research and review articles on diabetes by Cuban authors in journals listed in the Scopus bibliographic database, as well as related collaboration among Cuban institutions and between Cuban and non-Cuban institutions. METHODS A bibliometric analysis was conducted using 2000–2017 data from the Scopus database. The following search strategy was used: descriptor (diabetes), country (Cuba), publication source (journal), article type (original research, review article). Bibliographic indicators of production, visibility, impact and collaboration were examined. RESULTS Cuba contributed 3.2% of Latin American production and 0.1% of global production related to diabetes. Within Cuba’s scientific production (610 articles, 538 original research and 72 review), 85.9% had a Cuban corresponding author (Cuban leadership). In articles with international collaboration (22.9%), however, most (67.9%) had non-Cuban corresponding authors. A total of 47% (287) were articles involving a single institution. Only 11.1% were published in top-ranked journals, and 14.4% were cited >10 times. Cubans were lead authors on 0.3% of the most frequently cited (top 10%) articles on diabetes in Scopus. A total of 38.4% of this production appeared in low-impact journals and 57.9% in Cuban journals. Articles published in English accounted for 30% of total and obtained higher impact in terms of citations than articles in Spanish. The strongest networks for scientific collaboration were those that connected Cuban and US researchers.